2006
DOI: 10.21248/zaspil.44.2006.295
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the Sinn und Bedeutung 10

Abstract: ZASPiL 44(1).2006 contains 18 articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In Section 6, we imagined our two camps not being content with this annoyingly philosophical outcome, and wondered what arguments there might be to favor the grammar schema Ext over NExt or vice versa, arguments that would then indirectly 31 The central insight of this proposal, as we see it, is that in the case of physical ostension, the identification of the relevant object can be construed as an entirely rule-based, grammaticalized mechanism rather than a more or less free-wheeling attempt to guess the speaker's referential intention. 32 Basically the same analysis is independently suggested by Ebert et al [4]. They, too, work in a dynamic framework; the projection of their analysis of deictic utterances into our setting gives essentially ∃v i (vi = d ∧ φ) rather than our Dv i φ, where again it is assumed that I(d ) = I(D) (cf.…”
Section: For Quantifier Symbolsmentioning
confidence: 86%
See 2 more Smart Citations
“…In Section 6, we imagined our two camps not being content with this annoyingly philosophical outcome, and wondered what arguments there might be to favor the grammar schema Ext over NExt or vice versa, arguments that would then indirectly 31 The central insight of this proposal, as we see it, is that in the case of physical ostension, the identification of the relevant object can be construed as an entirely rule-based, grammaticalized mechanism rather than a more or less free-wheeling attempt to guess the speaker's referential intention. 32 Basically the same analysis is independently suggested by Ebert et al [4]. They, too, work in a dynamic framework; the projection of their analysis of deictic utterances into our setting gives essentially ∃v i (vi = d ∧ φ) rather than our Dv i φ, where again it is assumed that I(d ) = I(D) (cf.…”
Section: For Quantifier Symbolsmentioning
confidence: 86%
“…This is what we propose to do in this essay. 3 That contradictory answers should have been given is the more surprising in light of the fact that the two parties appear to agree on what we might call the generating syntax (i.e., the inductive definition of the well-formed expressions, particularly of quantified formulas), the ingredients for the semantic evaluation of well-formed expressions (to wit, model-theoretic structures and variable assignments), and the recursive (Tarskian [23]) steps to be taken in evaluating expressions relative to structures and variable assignments, as well as, presumably, on what it takes for well-formed expressions to be coextensive: 4 • Two sentences are coextensive if and only if they are both true or both false.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a large body of empirical evidence showing that referential manual gestures performed during speech tend to mark the introduction of new referents (e.g., Debreslioska et al, 2013;Ebert et al, 2011, Gullberg, 2003Levy & Fowler, 2000;Levy & McNeill, 2009;Marslen-Wilson et al, 1982;Yoshioka, 2008) and accessible referents (Debreslioska & Gullberg, 2020, 2022Rohrer, 2022), only a few studies have looked at the potential joint effects of prosody and gesture, what we also call multimodal marking. Türk (2020) investigated the multimodal marking of information structure in Turkish and found that both referential and non-referential manual gestures were systematically synchronised with pitch accents and tended to be paired with foci and contrastive elements.…”
Section: Prosodic Marking Of Information Status In a Foreign Languagementioning
confidence: 99%
“…Co-speech gestures —gestures temporally aligned with spoken content—serve a variety of purposes, including lightening the cognitive burden of language production (Gillespie et al, 2014; Goldin-Meadow et al, 2001; Krauss, 1998), marking information-structural features like focus (Ebert et al, 2011; Wilmes, 2009), and contributing additional meaningful content to the speaker’s utterance. An instance of the latter use of gestures can be seen in (1), in which the upwards-pointing gesture up coincides with the verb phrase “use the stairs,” generating an inference that the girl will take the stairs upwards:(1) The girl will [use the stairs] up .⤳The girl will go up the stairs.…”
Section: Introductionmentioning
confidence: 99%